ANALISIS KEMANDIRIAN BELAJAR MAHASISWA PGSD ANGKATAN 2020 PADA MATA KULIAH STATISTIK PENDIDIKAN - Nurhasmiranti; Qurrota Akyuni Azzahra; Setia Febriani Hammy; Jesi Alexander Alim (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2022)
The Education Statistics course is a basic part of arithmetic. Statistics courses are available in almost every college. Studying in Higher Education places great emphasis on the aspect of independence. In this article, researchers will analyze the learning independence of 2020 PGSD Study Program students in the Education Statistics course. The data collection technique used is random sampling with a questionnaire in the form of a Google Form. The research subjects in this article were 2020 PGSD Study Program students. The method used is a quantitative descriptive method. The results showed that the level of learning independence of PGSD Study Program students class of 2020 in the Education Statistics course was in the high category, on the six indicators of student learning independence, namely independence from others by 68.3% in the high category, having self-confidence of 54 .8% is in the fairly high category, 82.1% disciplined behavior is in the high category, 75.2% has a sense of responsibility in the high category, 66.4% self-initiated behavior is in the high category, and exercising self-control by 61.8% is in the high category.